2020
DOI: 10.1371/journal.pmed.1003369
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic level and associations between heat exposure and all-cause and cause-specific hospitalization in 1,814 Brazilian cities: A nationwide case-crossover study

Abstract: Background Heat exposure, which will increase with global warming, has been linked to increased risk of a range of types of cause-specific hospitalizations. However, little is known about socioeconomic disparities in vulnerability to heat. We aimed to evaluate whether there were socioeconomic disparities in vulnerability to heat-related all-cause and cause-specific hospitalization among Brazilian cities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 51 publications
3
41
0
1
Order By: Relevance
“…Psychiatric hospital admissions associated with temperature and heat waves were frequently studied ( n = 15). These studies demonstrate a positive association, particularly with elevated temperatures, with susceptibility varying in terms of demographic variables (e.g., older people shown to be at higher risk) [ 50 , 51 ] and type of disorder (e.g., organic disorders such as dementia) [ 52 ]. The relationship between hospital admissions and heat has been examined for a range of mental and neurological disorders, including dementia, mood disorders, anxiety disorders, schizophrenia, bipolar disorder, somatoform disorders, and disorders of psychological development [ 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Psychiatric hospital admissions associated with temperature and heat waves were frequently studied ( n = 15). These studies demonstrate a positive association, particularly with elevated temperatures, with susceptibility varying in terms of demographic variables (e.g., older people shown to be at higher risk) [ 50 , 51 ] and type of disorder (e.g., organic disorders such as dementia) [ 52 ]. The relationship between hospital admissions and heat has been examined for a range of mental and neurological disorders, including dementia, mood disorders, anxiety disorders, schizophrenia, bipolar disorder, somatoform disorders, and disorders of psychological development [ 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consistently with our results, a nationwide study in Brazil also found insignificant differences in heat–hospitalization associations for urologic diseases between lower-middle-income cities at 9.6% (6.2–13.1%) increase per 5°C increase in the daily mean temperature during the hot season and high-income cities at 4.9% (1.8–8.0%) increase per 5°C increase in the daily mean temperature during the hot season. 47 This is inconsistent with the general impression that low socio-economic status reflects a low educational level, limited use of air conditioning or no health insurance, which may exacerbate the heat effect. The inconsistency is speculated to be modified by the difference in population characteristics and other country- or region-specific factors.…”
Section: Discussionmentioning
confidence: 97%
“…The mental health outcome measures the effects of the environmental exposure, such as hospital admissions, mortality, symptom scales, screening tools, and self-harm. The studies that utilize hospital admission as mental health outcomes routinely collected administrative data [ 45 48 ]. From the mental health outcome perspective used to measure those environmental exposures to depression, hospital admission is the most considered variable, followed by symptom scales and emergency department visits to verify the depression morbidity.…”
Section: Resultsmentioning
confidence: 99%
“…e studies that utilize hospital admission as mental health outcomes routinely collected administrative data [45][46][47][48]. From the mental health outcome perspective used to measure those environmental exposures to depression, hospital admission is the most considered variable, followed by symptom scales and emergency department visits to verify the depression morbidity.…”
Section: Mental Health Outcomementioning
confidence: 99%